2022
DOI: 10.3389/fpsyg.2022.792872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed-Wave Chromotherapy and Guided Relaxation on the Theta-Alpha Oscillation During Arrest Reaction

Abstract: The search for the best wellness practice has promoted the development of devices integrating different technologies and guided meditation. However, the final effects on the electrical activity of the brain remain relatively sparse. Here, we have analyzed of the alpha and theta electroencephalographic oscillations during the realization of the arrest reaction (AR; eyes close/eyes open transition) when a chromotherapy session performed in a dedicated room [Rebalance (RB) device], with an ergonomic bed integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…Because it has been shown that the Rebalance ® program can have delayed effects [16], a second post-assessment was carried out one week after the first session for the G-Int only.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it has been shown that the Rebalance ® program can have delayed effects [16], a second post-assessment was carried out one week after the first session for the G-Int only.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…Each session of neuro-meditation was performed by means of the Rebalance ® device. Rebalance ® is a non-invasive cognitive stimulation and mindfulness training device based on the latest advances in the applied neuroscience [11,16]. During the sessions, the participants lay down in a "zero gravity" position (Figure 1B).…”
Section: The Rebalance Programmentioning
confidence: 99%
“…Consequently, when challenged with a stressor, MBI can reduce the impact of stress-related responses, such as disrupted sleep that are related to autonomic dysregulation ( Meerlo et al, 2008 ). Evidence suggests that neuro-meditation using the Rebalance© Impulse significantly increases the time spent in the theta–alpha oscillation power spectrum compared to a matched control ( Cheron et al, 2022 ). While speculative, this observation suggests that the improved sleep and cardiac regulation reported in the present study may be due to the Rebalance© Impulse enabling the participants to experience a greater amount of theta activity.…”
Section: Discussionmentioning
confidence: 99%
“…The G-con group did not receive any treatment. Rebalance© Impulse is a non-invasive cognitive stimulation and mindfulness training device based on applied neuroscience ( Creswell, 2017 ; Cheron et al, 2022 ). During the session, participants lied down in a “zero gravity” position ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation